Association between specimen length and diagnostic yield of temporal artery biopsy. (4th May 2017) - Grossman, C; Ben-Zvi, I; Barshack, I; Bornstein, G
Abstract : Objectives : Temporal artery biopsy (TAB) is performed in patients suspected of giant cell arteritis (GCA). Inadequate TAB specimen length is considered a possible explanation for a negative biopsy in patients with GCA. We investigated the association between specimen length and diagnostic yield of TAB. Method : We conducted a retrospective analysis of 240 patients who underwent TAB in a single hospital between 2000 and 2015. Patients were diagnosed with GCA based on positive TAB or, when TAB was negative, on clinical grounds that fulfilled the American College of Rheumatology (ACR) 1990 criteria. Baseline clinical and laboratory features and TAB length were obtained from medical records. Among patients diagnosed with GCA, the rate of TAB positivity was calculated according to biopsy length (< 5, 5–9, 10–14, and ≥ 20 mm). Results : Out of 240 patients, 88 were diagnosed with GCA: 62 had a positive TAB and 26 were diagnosed based on clinical grounds despite a negative TAB. Among those who were diagnosed with GCA, the length of the TAB specimen was similar in those with a positive and a negative TAB (1.13 ± 1.68 mm vs. 1.15 ± 0.61 mm, respectively, p = 0.928). The TAB positivity rate was similar among all ranges of biopsy length [< 5 mm: 7/10 (70%); 5–9 mm: 22/31 (71%); 10–14 mm: 11/16 (69%); 15–19 mm: 11/16 (69%); ≥ 20 mm: 11/15 (73%, p = ns] and was similar to the overall biopsy positivity rate. Conclusions : Specimen length is not associated with diagnostic yield of TAB.